2014
DOI: 10.5430/crcp.v2n1p61
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental findings of children with celiac disease in Libya: a comparative study

Abstract: Background and objectives: Celiac disease is a disease affecting the digestive system whereby the patient is unable to tolerate gluten-containing food. The aims of this study were to study the prevalence of dental defects and oral hygiene status of a group of celiac disease patients in Benghazi. Materials and methods: A group of celiac disease patients (n = 40 & Male: Female ratio is 1: 2.4 & age range 3-19 years, mean 10 years, SD ± 4.8) were recruited from Benghazi Pediatric Hospital where they had already b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…There is strong evidence confirming an increased risk of dental enamel defects (DED) in children with CD and it may be the only presenting symptom (1,77) . The incisors and molars are the most frequently affected (77)(78)(79) . We report a 2.5% prevalence of DED, but three case-control studies have reported estimates of 55%, 62% and 73% (as compared with 18%, 21% and 0% in the corresponding control groups), indicating higher prevalence of DED among children with CD (77)(78)(79) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is strong evidence confirming an increased risk of dental enamel defects (DED) in children with CD and it may be the only presenting symptom (1,77) . The incisors and molars are the most frequently affected (77)(78)(79) . We report a 2.5% prevalence of DED, but three case-control studies have reported estimates of 55%, 62% and 73% (as compared with 18%, 21% and 0% in the corresponding control groups), indicating higher prevalence of DED among children with CD (77)(78)(79) .…”
Section: Discussionmentioning
confidence: 99%
“…The incisors and molars are the most frequently affected (77)(78)(79) . We report a 2.5% prevalence of DED, but three case-control studies have reported estimates of 55%, 62% and 73% (as compared with 18%, 21% and 0% in the corresponding control groups), indicating higher prevalence of DED among children with CD (77)(78)(79) . A significant improvement on GFD in children with DED and CD is reported, so screening for CD is highly recommended, particularly in the presence of hypocalcemia (78,80) .…”
Section: Discussionmentioning
confidence: 99%